JPH3 Repeat Expansions Cause a Progressive Akinetic-Rigid Syndrome with Severe Dementia and Putaminal Rim in a Five-Generation African-American Family - Schneider, Susanne A. (2012)
We report the clinical, neuropsychological, genetic and radiological features of a large five-generation African-American kindred from the southern United States presenting with a progressive akinetic-rigid syndrome and severe dementia, but clinically insignificant chorea, due to mutations in JPH3. Overt disease onset was in the mid-twenties to late thirties with cognitive decline, REM sleep disturbance or psychiatric features, followed by development of a levodopa-unresponsive akinetic-rigid motor syndrome. Dystonia and myoclonus were present in some subjects. A bedridden, non-verbal severely akinetic-rigid state developed within 10 to 15 years after onset. CTG repeat expansions ranged from 47 to 53. Imaging revealed generalized cerebral atrophy with severe striatal involvement and putaminal rim hyperintensity. Analysis of our kindred indicates that JPH3 mutations should be considered in the differential diagnosis of early-onset dementia and hypokinetic-rigid syndromes in individuals of African descent. Moreover, chorea may not be overtly manifest at presentation or during significant parts of the disease course.